Corpus stylistics : speech, writing and thought presentation in a corpus of English writing - Semino, Elena, 1964- (Routledge advances in corpus linguistics, 2004)
This book combines stylistic analysis with corpus linguistics to present an innovative account of the phenomenon of speech, writing and thought presentation - commonly referred to as 'speech reporting' or 'discourse presentation'. This new account is based on an extensive analysis of a quarter-of-a-million word electronic collection of written narrative texts, including both fiction and non-fiction. The book includes detailed discussions of:The construction of this corpus of late twentieth-century written British narratives taken from fiction, newspaper news reports and)